2010
DOI: 10.1136/oem.2009.051342
|View full text |Cite
|
Sign up to set email alerts
|

Allergen and endotoxin exposure in a companion animal hospital

Abstract: Allergen exposure likely occurs during veterinary practice, with relatively low endotoxin levels. Future research should investigate dose-response relationship between airborne allergen exposure and health effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
48
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 39 publications
8
48
1
Order By: Relevance
“…The quantities of Ory c 3 (2.6-112.7 mg/m 2 ) are in the same order of magnitude as those of Fel d 1 and Can f 1 detected in settled dust of a companion animal hospital. 31 Up to 0.5 mg/m 2 Fel d 1 and up to 12 mg/ m 2 Can f 1 were obtained by using the electrostatic dust fall collection method. Another study analyzing allergen levels in different dog breeds found 5 to 9 mg/m 2 Can f 1 in settled house dust.…”
Section: Discussionmentioning
confidence: 99%
“…The quantities of Ory c 3 (2.6-112.7 mg/m 2 ) are in the same order of magnitude as those of Fel d 1 and Can f 1 detected in settled dust of a companion animal hospital. 31 Up to 0.5 mg/m 2 Fel d 1 and up to 12 mg/ m 2 Can f 1 were obtained by using the electrostatic dust fall collection method. Another study analyzing allergen levels in different dog breeds found 5 to 9 mg/m 2 Can f 1 in settled house dust.…”
Section: Discussionmentioning
confidence: 99%
“…The technique correlates moderately to well with active airborne sampling. 14,15 It is difficult to compare the SAD levels with other studies due to different techniques used. Only 1 study on dog allergens was performed with the EDC before, 15 which measured Can f 1 in an animal clinic.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 It is difficult to compare the SAD levels with other studies due to different techniques used. Only 1 study on dog allergens was performed with the EDC before, 15 which measured Can f 1 in an animal clinic. Although that was a different setting, found levels of airborne exposure were in the same range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive sampling of settled dust makes use of specific materials such as aluminum foil-covered pizza boxes (21), threedimensional polyurethane foam (31), or electrostatic dust clots and wipes (20,32).…”
Section: Settled and Reservoir Dust Samplingmentioning
confidence: 99%